Provide Instructors with A Learning Experience That is Fun, Convenient, and Enjoyable For Students - Suwarni Suwarni; Srikandi Dwi Poncowati; Eka Supriatna; Dede Kurnia Adiputra; Hernita Pasongli (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
An engaging, enjoyable, and comfortable learning method is presented in this study. A research method emphasizing literature reviews of scholarly books and journals was used in this study. For teachers seeking to improve instructional methods in elementary schools, the results of this study can be a valuable resource. This research identifies methods, characteristics, and factors that can optimize students' ability to learn and motivate, resulting in a fun, comfortable, and enjoyable learning experience. Through the consideration of individual differences in the classroom and the school, it is hoped that this research will increase the learning motivation of students. The study demonstrates the importance of the role of the teacher in using effective learning techniques so that students can develop their potential in a comfortable and pleasant learning environment. The purpose of this research is to identify the teacher's role in enhancing students' learning activities through the use of engaging teaching methods and learning principles. Schools should provide a comfortable learning environment where students can explore new, life-relevant ideas.